Genome-Wide Association Study and FST Analysis Reveal Four Quantitative Trait Loci and Six Candidate Genes for Meat Color in Pigs - Liu, Hang; Hou, Liming; Zhou, Wuduo; Wang, Binbin; Han, Pingping; Gao, Chen; Niu, Peipei; Zhang, Zongping; Li, Qiang; Huang, Ruihua; Li, Pinghua (Frontiers in Genetics, 2022)
Meat color is the primary criterion by which consumers evaluate meat quality. However, few candidate genes and molecular markers of meat color traits were reported for pig molecular breeding. The purpose of the present study is to identify the candidate genes affecting meat color and provide the theoretical basis for meat color molecular breeding. A total of 306 Suhuai pigs were slaughtered, and meat color traits were evaluated at 45min and 24h using CIELAB. All individuals were genotyped using GeneSeek GGP-Porcine 80 K SNP BeadChip. The genomic estimated breeding values (GEBV), heritability and genetic correlation of meat color traits were calculated by DMU software. The genome-wide association studies (GWAS) and the fixation index (FST) tests were performed to identify SNPs related to meat color, and the candidate genes within 1Mb upstream and downstream of significant SNPs were screened by functional enrichment analysis. The heritability of L* 45min, L* 24h, a* 45min, a* 24h, b* 45min and b* 24h was 0.20, 0.16, 0.30, 0.13, 0.29 and 0.22, respectively. The genetic correlation between a* (a* 45min and a* 24h) and L* (L* 45min and L* 24h) is strong, whereas the genetic correlation between b* 45min and b* 24h is weak. Forty-nine significant SNPs associated with meat color traits were identified through GWAS and FST tests. Among these SNPs, 34 SNPs were associated with L* 45min within a 5 Mb region on SSC11; 22 SNPs were associated with a* 45min within a 14.72 Mb region on SSC16; 6 SNPs were associated with b* 45min within a 4.22 Mb region on SSC13; 11 SNPs were associated with b* 24h within a 2.12 Mb region on SSC3. These regions did not overlap with QTLs reported relate with meat color. Moreover, 6 candidate genes (HOMER1, PIK3CG, PIK3CA, VCAN, FABP3 and FKBP1B) functionally related to muscle development, phosphatidylinositol phosphorylation and lipid binding were detected around the significant SNPs. Taken together, our results provide a set of potential markers for the genetic improvement of meat color in pigs and will advance the genome selection process of meat color on pig breeding programs.